Vertical CdTe:PVP/p-Si-Based Temperature Sensor by Using Aluminum Anode Schottky Contact - Cetinkaya, Hayriye Gokcen; Cicek, Osman; Altindal, Semsettin; Badali, Yosef; Demirezen, Selcuk (Institute of Electrical and Electronics Engineers (IEEE), 2022)
IEEEThe vertical Schottky barrier diode (SBD)-based temperature sensors with the drive modes is a significant issue with more advantageous than the on-chip sensor. The sensitivity (S) and the current conduction mechanisms (CCMs) of the vertical CdTe:PVP/p-Si SBD were studied experimentally over the range of 80–340 K and compared with that of the lateral and vertical sensors. It is shown that the low and moderated voltages of CdTe:PVP/p-Si corresponding two linear-regions of the current-voltage (I-V) outputs are around 0.1 - 0.3V and 0.4 - 0.65V, respectively. The variation of Schottky barrier height (ΦBo) and ideality factor (n) with temperature was obtained according to two linear-regions. Energy dispersion of the interface-traps (Nss) with changing temperature is additionally analyzed quantitatively. It is concluded that the thermionic-emission (TE) theory with Double-Gaussian distribution are the dominant mechanism resulting the I-V characteristics of the vertical CdTe:PVP/p-Si SBD in this study. Moreover, in constant current, the S values at the drive current of 10μA, 20μA and 50μA were resulting in a range of -1.6 to -1.8 mV/K.
Keywords: Current conduction mechanisms (CCMs), Schottky contact, temperature sensor, vertical diode; 7. Clean energy